2017
DOI: 10.1186/s12879-017-2348-2
|View full text |Cite
|
Sign up to set email alerts
|

TST positivity in household contacts of tuberculosis patients: a case-contact study in Malawi

Abstract: BackgroundScreening household contacts of active tuberculosis (TB) patients is recommended for TB control. Due to resource constraints this rarely occurs in lower income countries. Demographic and clinical features of index cases may influence the likelihood of onwards TB transmission. It has also been proposed that accumulation of intracellular lipid bodies within M. tuberculosis cells may also enhance bacterial transmissibility. This study explored whether clinical and bacteriological observations recorded a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
1
8
0
1
Order By: Relevance
“…The finding of a total of eight children with TB was close to the 10% target of total TB patients found. Other studies also reported a high level of TB case finding among children during contact investigation [27,28]. The prevalence of childhood TB among child contact tracing was also high [29].…”
Section: Discussionmentioning
confidence: 88%
“…The finding of a total of eight children with TB was close to the 10% target of total TB patients found. Other studies also reported a high level of TB case finding among children during contact investigation [27,28]. The prevalence of childhood TB among child contact tracing was also high [29].…”
Section: Discussionmentioning
confidence: 88%
“…This is unlikely to explain screening and treatment implementation within the cohort at IBIT, given the high percentage of patients who initiated and completed LTBI treatment. A study in Malawi identified that LTBI treatment in children was hampered by a lack of materials to perform TST and equipment to perform diagnostic x-ray examination, although a shortage of trained personnel to interpret TST results and high workload of health care professionals appeared to be the most important barriers (Hector et al, 2017). These observations strongly support the idea that optimization of TB screening and implementation of treatment for LTBI in children is crucial, particularly in those who are household contacts of those with active TB.…”
Section: Discussionmentioning
confidence: 99%
“…Trained laboratory technicians measured the induration after 48–72 hours, and results were subsequently validated by senior pediatricians at the study sites. A positive test result was defined as any induration greater than 10 millimeters [ 6 ].…”
Section: Methodsmentioning
confidence: 99%